DIPG-31. FEASIBILITY OF HYPERPOLARIZED 13C METABOLIC IMAGING IN PEDIATRIC PATIENTS WITH DIPG AND OTHER CNS CANCERS. (23rd April 2019) - Autry, Adam; Park, Ilwoo; Chen, Hsin-Yu; Gordon, Jeremy; Kline-Nunnally, Cassie; Vigneron, Daniel; Lupo, Janine; Li, Yan; Xu, Duan; Mueller, Sabine
Abstract: INTRODUCTION: As DIPG-tailored therapies become available in the future, the pediatric oncology community will need to address a longstanding issue regarding the lack of imaging biomarkers for evaluating response to treatment. Dynamic hyperpolarized carbon-13 ( 13 C) MR imaging offers a non-invasive means of probing real-time metabolism in vivo and has already been applied in adult patients with glioma (Park et al., MRM 2018; Keshari et al. Cancer Research 2018). The purpose of the current work was to evaluate the feasibility of this technique in pediatric patients and compare metabolism in normal-appearing white matter (NAWM) with adults. METHODS: Six pediatric patients (1 female, 5 males; ages 9–17) previously diagnosed with DIPG ( n =3), pineoblastoma ( n =1), medulloblastoma ( n =1), or adamantinomatous craniopharyngioma ( n =1) received dynamic 13 C MR imaging exams following intravenous injection of hyperpolarized [1- 13 C]pyruvate at 1–3 mL/s (0.43mL/kg). MR sequences consisted of either echo-planar imaging or echo-planar spectroscopic imaging, with 3.38-8cm 3 spatial resolution and 3s temporal resolution. Pre/post-injection EKGs and continuous vital sign measurements enabled close monitoring of patient response to the hyperpolarized contrast agent. All patients had previous radiation treatment (50-60Gy) and underwent diverse therapies; only 2 patients (DIPG) were surgery-naive. Conversion of [1- 13 C]pyruvate to [1- 13 C]lactate was kinetically modeled as a rate constant (kPL ) in NAWM using established methodology. RESULTS: There were no adverse effects in patients following injection of [1- 13 C]pyruvate. The apparent rate constant (kPL ) in this pediatric cohort was 0.022±0.007s -1 (range:0.014–0.030s -1 ), which was similar to adult patients with glioma treated by radiation (0.021±0.005). In one surgery-naïve patient with DIPG who received a higher resolution exam, two adjacent voxels in the T2 lesion demonstrated a 176–220% increase in kPL relative to NAWM. CONCLUSION: Initial results suggest hyperpolarized 13 C MR imaging can be safely performed in pediatric patients with CNS cancers and may augment treatment surveillance.